2010
DOI: 10.1097/pcc.0b013e3181b063e1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of bacteremia in infants with diarrhea and systemic inflammatory response syndrome attending an urban diarrheal treatment center in a developing country*

Abstract: Our data suggest that, in infants presenting with diarrhea and systemic inflammatory response syndrome, coexistence of hypothermia and absent or uncountable peripheral pulse is strongly associated with bacteremia. Bacteremia in this patient group is associated with high case-fatality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 29 publications
4
48
1
Order By: Relevance
“…The independent association of ileus with children being reluctant to feed is also understandable. Children with diarrhea and severe malnutrition who were reluctant to feed, more often presented with severe gut infection, leading to an edematous small bowel [18]. This phenomenon might contribute to the narrowing of the small bowel lumen and gaseous abdominal distension resulting in ileus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent association of ileus with children being reluctant to feed is also understandable. Children with diarrhea and severe malnutrition who were reluctant to feed, more often presented with severe gut infection, leading to an edematous small bowel [18]. This phenomenon might contribute to the narrowing of the small bowel lumen and gaseous abdominal distension resulting in ileus.…”
Section: Discussionmentioning
confidence: 99%
“…Septic shock was defined as severe sepsis that was unresponsive to fluid resuscitation. Severe sepsis in diarrheal children has been defined in recent publications from Bangladesh [14,16]; originally adopted from the surviving sepsis guideline recommended by the American Pediatric Association [17,18], with minor modifications for children with diarrhea. Severe sepsis was defined as sepsis plus the presence of poor peripheral perfusion (weak or absent peripheral pulses), and a capillary refilling time greater than 3 seconds or age-specific hypotension.…”
Section: Methodsmentioning
confidence: 99%
“…The observed bacteraemia due to coagulase-negative S. aureus might represent community-acquired pneumonia, which is not uncommon in severely-malnourished children (24). Such children are often deficient in alveolar type II cells and complement, leading to inability to efficiently clear Staphylococcus from their lungs (25) and better survival of the pathogen in alveolar lining epithelial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Increased number of immature neutrophils in the peripheral blood smears of children is an expression of severe illness common in bacterial sepsis [1]. An earlier study from Bangladesh reported that children with leukocytosis and immature neutrophils in their peripheral blood are more likely to be bacteremic and to have a higher risk of death [1]. Thus, the presence of immature neutrophils in peripheral blood in diarrheal children should alert clinicians to look for sepsis in order to reduce morbidity and deaths in such population.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is one of the most important causes of death in under-five children in developing countries [1,2]. The largest part of the global sepsis burden occurs in middleand low-income countries.…”
Section: Introductionmentioning
confidence: 99%